Yobuko morning market in Saga Prefecture, Japan: Its character as sustainable and creative place - A. Harisah; A.N Kakon; N. Mishima; T. Arima (Lowland Technology International, 2016)
The intention of the research is to identify several characteristics of Yobuko Morning Market (YMM) and to seek the reason why the market is still survive until now so that we can describe the uniqueness of the market and the reason of the market is still survive even though there are many alternative shopping places from reality to cyber world in around it. The research used concept of sustainable, creative, and diverse places to analysis the YMM, and several research methods to collect the data: 1). questionnaire, 2) structured interview, 3) unstructured observation, and 4) secondary data. The result research described several characteristics inter alia: temporary setting with shop-house in the background and only could be found at 7.00-12.00 in every day, dominated old women sellers and consumers, dominated specific food either squid fresh foods or processed foods, specific selling system: fixed price and sometimes they add goods depend on the seller, etc. Besides those, they also prepare barbecue for consumers, and create new products from squids at the place for new identity, and also we found several indications of sustainable and creative place and vice versa.